Is That Your Child?: Mothers Talk about Rearing Biracial Children - Kilson, Marion; Ladd, Florence (Lexington Books, 2008)
Is That Your Child?' is a question that countless mothers of biracial children encounter whether they are African American or European American, rearing children today or a generation ago, living in the city or in the suburbs, are upper middle class or lower middle class. Social scientists Marion Kilson and Florence Ladd probe mothers' responses to this query and other challenges that mothers of biracial children encounter. Organized into four chapters, the book begins with Kilson and Ladd's initial interview of one another, continues with an overview of the challenges and rewards of raising biracial children gleaned from their interviews with other mothers, presents profiles of mothers highlighting distinctive individual experiences of biracial parenting, and concludes with suggestions of positive biracial parenting strategies. This book makes a unique contribution to the growing body of literature by and about biracial Americans. Although in the past twenty years biracial Americans like Rebecca Walker, June Cross, and James McBride have written of their person experiences and scholars like Kathleen Korgen, Maria Root, and Ruth Frankenberg have explored aspects of the biracial experience, none has focused on the experiences of a heterogeneous set of black and white mothers of different generations and socioeconomic circumstances as Kilson and Ladd do.